Ferulic acid esters of glucosylglucose from Allium macrostemon Bunge. Issue 3 (4th March 2017) - Usui, Ayaka; Matsuo, Yosuke; Tanaka, Takashi; Ohshima, Kazusato; Fukuda, Shinji; Mine, Takara; Yakashiro, Ichiro; Ishimaru, Kanji
Abstract: Three new ferulic acid esters of glucosylglucose, 1- O -( E )-feruloyl-β- d -glucopyranosyl (1-2)-[β- d -glucopyranosyl (1-6)]-β- d -glucopyranose (allimacronoid A, 1 ), 1- O -( E )-feruloyl-β- d -glucopyranosyl (1-4)-[β- d -glucopyranosyl (1-2)]-[β- d -glucopyranosyl (1-6)]-β- d -glucopyranose (allimacronoid B, 2 ), and 1- O -( E )-feruloyl-β- d -glucopyranosyl (1-6)-[β- d -glucopyranosyl (1-2)]-[β- d -glucopyranosyl (1-6)]-β- d -glucopyranose (allimacronoid C, 3 ) were isolated together with tuberonoid A (4 ), from the leaves of Allium macrostemon Bunge. The chemical structures were elucidated based on the analyses of the spectroscopic and chemical data.